SOME PROBLEMS OF DETAINEES AND PERSONS’ SENTENCED TO IMPRISONMENT NUMBER REDUCING IN THE RUSSIA FEDERATION - Rudnev, Vladimir (Administrative and Criminal Justice, 2019)
Some aspects оf criminal policy related to the number of detainees and persons convicted to imprisonment have been disclosed in the paper. The repressiveness’s increase of the Russian Federation Criminal code, which was adopted in 1996 has been discussed. The author has concluded that there is a necessity in reducing of the number of detainees and persons convicted to imprisonment in the Russia Federation. The negative consequences of detention and serving a sentence in jail have been emphasized. Courts’ work on the application of a preventive measures in the form of detention have been analyzed. The shortcomings of the Russian Federation of criminal-procedural legislation have been pointed out. The author pays attention on the extension of detention periods. It is concluded that there is necessity in strengthening of the court power. It is proposed to develop specialization of judges. The suggestion about introducing of the position of penitentiary judge has been supported. The decisions of European Court of Human Rights are provided. The suggestions for improvement of some federal laws are made. It is proposed to adopt a law about probation.